Panic or erect veldt grass Ehrharta erecta var. erecta (Ehrharteae, Oryzoideae, Poaceae): new records of an introduced genus in México in the states of Michoacán and Baja California - Sánchez-Ken, J. Gabriel (Phytotaxa, 2019)
Two new records of Ehrharta erecta are formally reported from the states of Michoacán and Baja California. This taxon is apparently a recent introduction to the Mexican flora since the dates of the specimens are from the last decade. With these records, the number of species of Flora del Bajío (Michoacán) and Baja California is increased. Based on the characteristics of the plants, the taxon growing in the Americas belongs to E. erecta var. erecta.